The Antarctic Treaty System: challenges and opportunities - Marcus Haward (2019)
Over the last 60 years, the scope of international governance of Antarctica has steadily expanded in scope. In 1959, during the geopolitical tension of the early cold-war period, the Antarctic Treaty was formed by the twelve original states to primarily prevent security competition in the Antarctic region. From its very creation, resolution – or at least management – of geopolitical tension has been a core norm of the Antarctic Treaty. This instrument was negotiated and entered into force during a period of heightened Cold War competition between the United States and the Soviet Union. The Antarctic Treaty effectively managed this tension by demilitarising the Antarctic continent and directing all human presence on the continent towards peaceful use and scientific research. Throughout its history the Antarctic Treaty has been viewed as a successful example of international governance because of its successful responses to internal and external pressures.